Aplikasi Yang Digunakan Guru Dalam Pembelajaran Dimasa Pandemik - Firmadini, Firmadini; Tisnasari, Oktifa (Journal of Development Education and Learning (JODEL), 2023)
Applications used by teachers in learning there are several kinds of applications that can be accessed via Android or computers as well as various kinds of functions and how to use them and these applications make it easier for teachers to deliver lessons remotely. The purpose of this study is 1) to find out what applications the teacher uses in the learning process 2) to determine the advantages and disadvantages of each application. The research method used is qualitative research which produces descriptive data which includes observation and interviews. the subject of this research is the teacher. The results of this study the teacher used distance learning media applications since the COVID-19 pandemic, basically the teacher experienced difficulties in the teaching process in the middle of Covid-19 until the teacher used the learning media application for the learning and teaching process remotely, in order to make it easier for students and teachers in the learning process, but on the other hand, many teachers experience difficulties in using the application. The conclusion in this study is that the application used by teachers in teaching and must accept the advantages and disadvantages of this application, this application is already running but not optimal and perfect, because there are still obstacles and limitations such as interference with the network.